BODIPY based A-D-A molecules: Effect of CF3 group substitution at meso phenyl group. (June 2020) - Tarafdar, Gourav; Johnson, Justin C.; Larson, Bryon W.; Ramamurthy, Praveen C.
Abstract: Two pairs of A-D-A molecules have been synthesized with fluorene and benzodithiophene as the central donor subunits and terminal BODIPY units, functionalized with either a 4-methylphenyl or 4-trifluoromethylphenyl group at the meso position. The effect of the para substituent of the meso phenyl group on the photophysical properties of these molecules is studied through steady state absorption and fluorescence spectroscopy as well as femtosecond transient absorption and time resolved fluorescence spectroscopy techniques. Applicability of these molecules as donors in solution processed solar cell active layers was investigated through time resolved microwave conductivity measurements on blends with PC60 BM acceptor, which shows a varying yield of charge transfer with choice of substituent. Transient absorption spectroscopy is then employed to investigate the role of the 4-trifluoromethylphenyl group in altering the efficiency of charge transfer from these A-D-A molecules to PC60 BM. The results show a consistent picture of picosecond charge transfer and a component of a few hundred ps geminate recombination that results in a small yield of long-lived free charges optimized for the methylphenyl derivatives. Highlights: Two pairs of new A-D-A dyes based on BODIPY have been synthesized and characterized. The effect of trifluoromethyl substituent on properties of BODIPY based dyes studied. Electron transfer studied using TRMC and TA measurements. Mechanism of electron transfer from BODIPY based A-D-A molecules to PC60 BM proposed. Trifluoromethyl substituent lowers electron transfer.